Análise de risco do investimento em ações de empresas agrícolas presentes na B³ - Ziegler, Cristiano (2019)
The financial area is important for the development of companies and countries, in need of improved investment techniques. The quest for profit in this market brings with it exposure to a certain level of risk that can be estimated by knowing the persistence of stock volatility. The present study has as main objective to estimate the persistence of the volatility of three agricultural companies, commercialized in B³, using linear and nonlinear modeling. To make this comparison possible, a statistical method, known as Box and Jenkins or ARIMA methodology, and autoregressive models with conditional heteroscedasticity (ARCH), is used. The study begins with a literature review, presenting the concepts of actions and their respective market, the Box-Jenkins models and methodology, the description of the ARCH family model method and recent studies on the subject. Then in the materials and methods, the classification of the research, the data collection with the description of the companies selected for the study and the methodological procedures used in the research are exposed. The share of results was through into two articles, in the first, is carried out the verification of persistence and the peaks of volatility in the stock price of the company SLC Agrícola. The study period was from January 1, 2011 until December 31, 2017. In the second article, it is estimated the persistence of volatility in the prices of three agricultural companies and the Ibovespa index. The period under analysis was from January 1, 2014 until December 31, 2017. At the end of the research, it was evident that the political and economic turbulence contributed to a high persistence of stock price volatility, even though they were similar companies, under the same external influences.